2021
DOI: 10.1111/jfpp.15449
|View full text |Cite
|
Sign up to set email alerts
|

Adequacy assessment of neuro‐fuzzy simulation system for characterization of hydration kinetics of sesame seeds subjected to thermic and ultrasonication schemes

Abstract: Neuro-fuzzy simulation of food engineering phenomena can be a supportive manner for integrated realization of compound trends of involved parameters. This paper is aimed to develop neuro-fuzzy simulation system for characterization of hydration kinetics of sesame seeds subjected to thermic and ultrasonication schemes. The simulation system was developed based on various types and numbers of input membership functions, defuzzification methods, types of output membership functions, and numbers of training cycles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 90 publications
0
8
0
Order By: Relevance
“…This mechanism creates microchannel, thus improving mass transfer (Miano et al, 2017). Similar studies dealt with ultrasound technology in water absorption process of agricultural products (Borsato, Jorge, Mathias, & Jorge, 2019; Guimaraes, Polachini, Augusto, & Telis‐Romero, 2020; Li et al, 2019; Miano et al, 2018; Miano, Rojas, & Augusto, 2019; Shafaei et al, 2021a; Shafaei et al, 2021b; Shafaei, Nourmohamadi‐Moghadami, & Kamgar, 2019; Shafaei, Nourmohamadi‐Moghadami, Rahmanian‐Koushkaki, & Kamgar, 2019; Yildirim et al, 2011; Yildirim, Bayram, & Mehmet, 2012; Yildirim, Öner, & Bayram, 2010) confirms this research. Increase in mass diffusion of cowpea during soaking may be decrease in cooking time of cowpea.…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…This mechanism creates microchannel, thus improving mass transfer (Miano et al, 2017). Similar studies dealt with ultrasound technology in water absorption process of agricultural products (Borsato, Jorge, Mathias, & Jorge, 2019; Guimaraes, Polachini, Augusto, & Telis‐Romero, 2020; Li et al, 2019; Miano et al, 2018; Miano, Rojas, & Augusto, 2019; Shafaei et al, 2021a; Shafaei et al, 2021b; Shafaei, Nourmohamadi‐Moghadami, & Kamgar, 2019; Shafaei, Nourmohamadi‐Moghadami, Rahmanian‐Koushkaki, & Kamgar, 2019; Yildirim et al, 2011; Yildirim, Bayram, & Mehmet, 2012; Yildirim, Öner, & Bayram, 2010) confirms this research. Increase in mass diffusion of cowpea during soaking may be decrease in cooking time of cowpea.…”
Section: Resultsmentioning
confidence: 92%
“…The increase in the temperature enhancements contraction and expansion process of kernels which drops diffusion resistance. Hence, water diffusion increases as the temperature increases, and consequently results in more absorption of water (Cheevitsopon & Noomhorm, 2011; Shafaei et al, 2021b; Shafaei, Nourmohamadi‐Moghadami, & Kamgar, 2021a; Sobukola & Abayomi, 2011).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, another strategy (ultrasonication) has been employed to proliferate water absorption of agricultural food products. Literature screening process confirmed that ultrasonication strategy was successfully utilized for soaking process of rice (Li et al, 2019;Wambura, Yang, & Wang, 2008), chickpea (Yildirim, Bayram, & Oner, 2012;Yildirim & Oner, 2015;Yildirim, Oner, & Bayram, 2010;Yildirim, Oner, & Bayram, 2011;Yildirim, Oner, & Bayram, 2013), bean (Ghafoor, Misra, Mahadevan, & Tiwari, 2014;Lopez et al, 2017;Miano & Augusto, 2018a;Miano, Pereira, et al, 2016;Miano, Rojas, & Augusto, 2019a;Miano, Sabadoti, & Augusto, 2018;Miano, Sabadoti, & Augusto, 2019;Ulloa et al, 2015), sorghum (Miano, Ibarz, et al, 2016;Patero & Augusto, 2015), melon (Miano, Ibarz, et al, 2016), sea cucumber (Zhang et al, 2016a(Zhang et al, , 2016b, carrot (Ricce, Rojas, Miano, Siche, & Augusto, 2016), corn (Miano, Ibarz, & Augusto, 2017), wheat (Guimaraes, Polachini, Augusto, & Telis-Romero, 2020;Shafaei, Nourmohamadi-Moghadami, & Kamgar, 2018;Shafaei, Nourmohamadi-Moghadami, Rahmanian-Koushkaki, & Kamgar, 2019), potato (Miano, Rojas, & Augusto, 2019b), barley (Borsato, Jorge, Mathias, & Jorge, 2019;Carvalho, Polachini, Darros-Barbosa, Bon, & Telis-Romero, 2018;, pumpkin (Rojas, Silveira, & Augusto, 2020), sesame (Shafaei, Nourmohamadi-Moghadami, et al, 2021), and paddy (Kalita, Jain, Srivastava, & Goud, 2021). In these works, modelin...…”
Section: Introductionmentioning
confidence: 92%